Sulfonamides quantification in milk by high performace liquid chromatography via azoderivatives - Marques, Marcelo Volpatto; Naciuk, Fabrício Fredo; Mello, Ana Maria de Souza; Seibel, Nair Maria; Santos, João Gabriel Rosa dos; Fontoura, Luiz Antonio Mazzini (Pesquisa Agropecuaria Brasileira, 2009)
The objective of this work was to evaluate an analytical method for the simultaneous measurement of sulfathiazole, sulfamethazine, and sulfadimethoxine in milk, in the form of azoderivatives, through the high performance liquid chromatography (HPLC). The isolation and concentration of sulfas were carried out by solid phase extraction (C18) with methanol as eluent. After extraction, analytes were transformed in diazonium salts and coupled with resorcinol. Derivatives were quantified by HPLC (C8 column, l = 430 nm, MeOH/KH2PO4 aq). Recoveries were obtained between 65 and 78%.